Perlindungan Hukum Pemegang Hak Guna Bangunan Atas Tanah Yang Musnah Akibat Abrasi Laut: Kajian Normatif Di Kabupaten Sidoarjo - Anindita Girindra Wardhani; Widyarini Indriasti Wardani (MAGISTRA Law Review, 2026)
This study profoundly examines the legal protection for holders of Building Rights (HGB) lost due to marine abrasion in Sidoarjo. Indonesia, as an archipelagic nation, faces severe coastal abrasion, leading to the disappearance of 656 hectares of HGB land in Segorotambak Village, owned by PT Surya Inti Permata and PT Semeru Cemerlang. This issue is exacerbated by regulatory gaps concerning HGB grants over sea surfaces and the mechanism for handling vanished land, creating legal uncertainty and substantial losses. Based on this background, the research formulates three main problems: (1) What is the legal status of HGB land lost due to marine abrasion in Sidoarjo? (2) What are the legal consequences for HGB holders whose land vanishes due to marine abrasion in Sidoarjo? and (3) How is legal protection provided to HGB holders whose land vanishes due to marine abrasion in Sidoarjo? The study employs a juridical-empirical method, integrating statutory, conceptual, and case approaches, with a descriptive-analytical specification. Primary data (interviews) and secondary data are qualitatively analyzed. he research findings indicate that the legal status of vanished HGB land is hapis demi hukum (null and void by law) due to the physical disappearance of the object, despite often remaining administratively recorded, creating a gap between das sollen (legal norms) and das sein (field reality). The legal consequences include loss of economic asset value and potential ongoing administrative burdens (e.g., land and building tax), with a goodwill fund scheme that fails to provide full compensation. The existing legal protection is formalistic and partial, where the priority right for reconstruction is difficult for right holders to access due to financial and technical constraints, as well as slow administrative mechanisms, highlighting significant weaknesses in substantive protection. This study underscores the urgency of reinterpreting the concept of vanished land and improving more adaptive and responsive regulations.